Numerical investigation of lithium-sulfur batteries by cyclic voltammetry. (February 2020) - Mačák, M.; Vyroubal, P.; Kazda, T.; Jaššo, K.
Highlights: Custom electrochemical model of Li-S cell implemented into Ansys Fluent. Cyclic voltammetry of planar electrode. Cyclic voltammetry of a single porous particle. Experimental measurement of Li-S cell. Comparison of numerical and experimental values. Abstract: The lithium-sulfur batteries have the potential to become a leading energy storage system as they are showing promising characteristics such as high theoretical capacity and energy density. However, their performance is hindered by poor cyclability, self-discharge and capacity loss. Numerical simulations of the processes occurring in lithium-sulfur batteries might bring a better understanding of the governing mechanisms, which will allow the necessary development of the applicable cells. This paper presents a custom electrochemical model of a lithium-sulfur cell implemented into Ansys Fluent. The model describes a multi-component transport of species through Nernst-Plank equations in a dilute solution. The redox mechanism was described through a multi-step mechanism, with kinetics being defined through the Butler-Volmer equation. The model was used to model cyclic voltammetry at a planar electrode and at single porous particles. The results indicate that the cyclic voltammetry response of the whole porous sulfur cathode could be solved as a response of a single particle, which might lead to a simplification of numerical simulations.